Increasing Literacy In Reading The Qur’an Hadith In Class IX Students Through The Application Of The Talaqqi Method At MTsN 1 Kudus - Rozaq, Mohammad Khoirur; Nugroho, Puspo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The focus of this research is to find out how the talaqqi method can improve students' reading literacy of the Al-Qur'an Hadith at MTs N 1 Kudus class IX. The subjects in this research involved Al-Qur'an Hadith subject teachers and class IX students. The method in this research uses a qualitative descriptive approach and data collection through interviews, observation and documentation. The results of this research can be concluded that the application of the talaqqi method in learning Al-Qur'an Hadith is considered effective in improving students' ability to read the Al-Qur'an. The talaqqi method is very suitable for use in learning the Al-Qur'an. The driving factors in implementing the talaqqi method at MTs N 1 Kudus, include; a) there are teachers who are qualified in their field of recitation, b) there is support from parents and teachers, and c) the conditions in the madrasa are comfortable and very supportive. The inhibiting factors include; a) less effective time management, b) the emergence of a feeling of laziness and lack of focus among students, and c) lack of support from students' parents. Communication between teachers and parents is the solution to this obstacle. It is hoped that this research will provide new knowledge and a deeper understanding regarding the application of the talaqqi method in increasing students' Al-Qur'an reading literacy and provide a basis for developing better talaqqi learning methods for teachers and students.